Salidroside protects endothelial cells against LPS-induced inflammatory injury by inhibiting NLRP3 and enhancing autophagy - Lijiao You; Di Zhang; Huan Geng; Fangyuan Sun; Ming Lei (BMC, 2021)
Abstract Background Salidroside (SAL) is a bioactive compound extracted from Rhodiola rosea with various biological properties. This study was designed to explore the functions of SAL on the endothelial damage induced by lipopolysaccharide (LPS) and its related mechanisms. Methods Human umbilical vein endothelial cells (HUVECs) were pretreated with SAL (0, 10, 25, 50, 100 μM), and then incubated with LPS (10 μg/mL). Cell viability was evaluated by MTT assay, cell injury by lactate dehydrogenase (LDH) release, and inflammatory cytokines release by ELISA assay. Oxidative stress was evaluated by malondialdehyde (MDA) and superoxide dismutase (SOD) in cell lysate. Apoptosis was detected by flow cytometry and caspase-3 activity. Western blot were performed to determine expression levels of autophagy and NOD-like receptor protein 3 (NLRP3) related proteins. Results SAL at 50 μM concentration showed no toxicity on HUVECs, but attenuated LPS-induced injury, as evidenced by increased cell viability, reduction in LDH level and inflammatory cytokines in culture media. SAL also reduced MDA level and increased SOD activity in HUVECs, and inhibited apoptosis rate and caspase-3 activity. (P < 0.05). Moreover, LPS enhanced HUVECs autophagy, and SAL pretreatment further enhanced autophagy, with increased Beclin-1 protein and decreased P62 protein. SAL also attenuated LPS-induced activation of NLRP3 inflammasome, reduced the protein expression of NLRP3-related proteins, including ASC and caspase-1. Autophagy inhibition by 3-MA markedly reversed SAL-modulated changes in cell viability and NLRP3 expression in LPS-stimulated HUVECs. Conclusion SAL protects endothelial cells against LPS-induced injury through inhibition of NLRP3 pathways and enhancing autophagy.